The role of school literature in shaping a Ukraine-centered identity of youth - Udovychenko Larisa; Удовиченко Лариса (Видавництво «Код», 2025)
Abstract. The primary goal of this article is to analyze and substantiate the significance of forming a Ukraine-centric identity sphere among Ukrainian schoolchildren as an essential foundation for the country’s continued European-oriented development, particularly relevant under current sociopolitical challenges intensified by Russia’s invasion. The methodology combines a comprehensive literature review and critical analysis of historical, philosophical, pedagogical, and methodological works by prominent Ukrainian and international scholars specializing in identity formation, educational philosophy, and literary teaching methodologies. Key theoretical insights and practical experiences regarding civic, cultural, and national identity integration into educational contexts are examined thoroughly. Results of the analysis highlight the effectiveness of structured methodological approaches that employ Ukrainian and world literature courses. Such methods significantly contribute to nurturing students’ critical thinking skills, intercultural respect, and active civic participation. The research identifies the need for an integrated pedagogical approach, which synergistically aligns literary education with national values, thus promoting students’ self-awareness, civic maturity, and social responsibility. Additionally, the study underscores the essential role educators play in fostering respectful, supportive, and empowering classroom environments, crucial for meaningful identity development. Conclusions drawn indicate that forming a Ukraine-centered identity is not only an educational imperative but a fundamental prerequisite for Ukraine’s sustainable societal growth and effective integration into the broader European community. Future research should focus on investigating deviations and challenges in identity formation processes and designing targeted educational interventions to mitigate negative influences from unreliable information and adverse social environments.

Резюме. У статті обґрунтовується значущість формування україноцентричної ідентичності серед учнівської молоді як ключової передумови сталого розвитку держави та її подальшої інтеграції до європейського простору. Методологія дослідження ґрунтується на поєднанні комплексного огляду наукової літератури та критичного аналізу історичних, філософських, педагогічних і методичних праць провідних вітчизняних і зарубіжних учених. Здійснено узагальнення теоретичних положень і практичного досвіду інтеграції громадянської, культурної та національної ідентичності в освітній процес.
Роль шкільного курсу літератури у формуванні україноцентричної ідентичності молоді
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-16?authuser=0
Keywords: civic competencies; cultural-national identity; European integration; identity formation; methodological approaches; Ukraine-centered education